Pengelolaan Risiko Produktifitas pada Usahatani Bawang Merah Pasca Covid-19 - Nurhapsa, N; Suherman, S (Journal Galung Tropika, 2023)
The COVID-19 pandemic that hit regions in Indonesia has limited community activities. This research was conducted in Mataran Village, Anggeraja District, Enrekang Regency, to analyze productivity risk management (ex-ante, post-Covid-19 shallot farming). The method in this research was quantitative descriptive with a sample size of 36 shallot farmers. The sampling technique used a simple random method (random sampling). The research results show that the respondent farmers' ex-ante risk management strategy is to carry out a planting pattern, namely shallots-shallots-shallots, with a monoculture system. The seeds used are sourced from other parties; generally, only one type of seed is planted for different lands. For interactive strategies used by respondent farmers, they are planting shallots at the end of the dry season before the rainy season, using organic and inorganic fertilizers, replanting if a plant dies, mixing pesticides to save costs and eradicate more pests and diseases. Meanwhile, ex-post risk management means that if the shallot farming business fails, the action taken by the farmer is to look for additional work but continue to plant shallots in an area adjusted to the available capital. If there is a lack of capital, the respondent farmers borrow from fellow farmers or families, and some borrow from farmer kiosks or banks. Therefore, it is hoped that the role of agricultural extension workers will be more optimal in helping shallot farmers manage productivity risks and access capital.